2014
DOI: 10.4236/ae.2014.23019
|View full text |Cite
|
Sign up to set email alerts
|

A Review of Agricultural Pesticides Use and the Selection for Resistance to Insecticides in Malaria Vectors

Abstract: Most national malaria control programmes rely extensively on pyrethroid insecticides to control mosquito vectors of this disease. Unfortunately, the intensive use of this class of insecticides both in public health and agriculture has led to its reduced efficacy. The objective of this review was to assess the role of agricultural pesticides use on the development of resistance to insecticides in malaria vectors and the potential impact of this resistance on control activities. We searched library catalogues an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
39
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 43 publications
(44 citation statements)
references
References 41 publications
5
39
0
Order By: Relevance
“…The farmers in the community also use cypermethrin, lambdacyhalothrin, deltamethrin, dichlovos and primiphos-methyl for agricultural crop protection. Previous researchers have reported that exposure of malarial vectors to crop protection insecticides could result in development of insecticide resistance (Etang et al, 2003;Awolola et al, 2007;Müller et al, 2008;Chouaibou et al, 2008;Bigoga et al, 2012;Philbert et al, 2014). LLIN was used in Misau for protection against mosquitoes since 2002 to date and it may induce selections to pyrethroids insecticides.…”
Section: Discussionmentioning
confidence: 99%
“…The farmers in the community also use cypermethrin, lambdacyhalothrin, deltamethrin, dichlovos and primiphos-methyl for agricultural crop protection. Previous researchers have reported that exposure of malarial vectors to crop protection insecticides could result in development of insecticide resistance (Etang et al, 2003;Awolola et al, 2007;Müller et al, 2008;Chouaibou et al, 2008;Bigoga et al, 2012;Philbert et al, 2014). LLIN was used in Misau for protection against mosquitoes since 2002 to date and it may induce selections to pyrethroids insecticides.…”
Section: Discussionmentioning
confidence: 99%
“…This could be ascribed to multiple confounding factors capable of complicating the interpretation of data. The most available evidence is laboratory or experimental huts-based and harnessing entomological outcomes to assess the impact resistance on mosquito biting rates, blood feeding rates, or insect mortality [153]. Conflicting findings on the impact of resistance on vectorial capacity has been reported with some results indicating an increasing effect [156][157][158][159][160] while others present decreasing outcomes [159,160].…”
Section: Resistance and Vector Controlmentioning
confidence: 81%
“…However, the impact of resistance on the ability of malaria control intervention to reduce disease transmission is poorly understood [153]. Insecticide resistance triggers a chain reaction that through deteriorated efficacy leads to vector control failure and disease control failure may be expected [153]. Evidence linking the potential of ITNs increasing phenotypic resistance and kdr frequency [154,155] that threaten to compromise their effectiveness exists [86].…”
Section: Resistance and Vector Controlmentioning
confidence: 99%
See 2 more Smart Citations